(untitled) - Wildfeuer, Janina (London, 2014)
This book contributes to the analysis of film from a multimodal and textual perspective by extending formal semantics into the realm of multimodal discourse analysis. It accounts for both the inferential as well as intersemiotic meaning making processes in filmic discourse and therefore addresses one of the main questions that have been asked within film theory and multimodal analysis: How do we understand film and multimodal texts? The book offers an analytical answer to this question by providing a systematic tool for the description of this comprehension process. It aims to advance knowledge of the various resources in filmic texts, the ways the resources work together in constructing meaning and the ways people understand this meaning construction. This new approach to film interpretation is thus able to remodel and improve the classical paradigm of film text analysis.
Keywords: Motion pictures and language,Phim ảnh và ngôn ngữ